2012
DOI: 10.1287/orsc.1110.0654
|View full text |Cite
|
Sign up to set email alerts
|

Not All Identifications Are Created Equal: Exploring Employee Accounts for Workgroup, Organizational, and Professional Identification

Abstract: Scholars are increasingly interested in understanding the content and process of employee identification. In this paper, I contribute to this discussion by performing a qualitative case study investigating the accounts employees provide as they make sense of their identification with their workgroup, organization, and profession. Analyses of accounts from 31 members of an architecture firm reveal nine explanations individuals use to make sense of their identifications, which can be categorized using four sense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
136
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(143 citation statements)
references
References 88 publications
4
136
0
3
Order By: Relevance
“…Eisenberger and Stinglhamber (2011) suggested that employees are well aware of and concerned about the care and value their organizations extended to them. In her qualitative study, Vough (2012) found that during the development of organizational identification, employees were sensitive to support (i.e. organization's concern for employees and willingness to act on their interests) in addition to organizational prestige.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Eisenberger and Stinglhamber (2011) suggested that employees are well aware of and concerned about the care and value their organizations extended to them. In her qualitative study, Vough (2012) found that during the development of organizational identification, employees were sensitive to support (i.e. organization's concern for employees and willingness to act on their interests) in addition to organizational prestige.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Vough (2012) inferred that employees rely on several sensemaking logics to establish their identification. She proposed that organizational identification stems from organizational ideology, prestige, support (i.e.…”
Section: Implications For Theory Practice and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were collected through observations, informal interactions and shadowing (Vough 2012). Observation included meetings with consultants and stakeholders, as well as internal team meetings, participation in site visits, design meetings, presentations and management meetings.…”
Section: Methodsmentioning
confidence: 99%
“…The complexity introduced by a multiple-identity perspective on the identification process is further complicated by activities that organizations engage in to sustain and promote a hybrid identity. Organizational sense-giving activities (Ashforth et al, 2008;Gioia & Chittipeddi, 1991;Vough, 2012) promoting one identity over another or designed to integrate or synthesize identities and thus influence an individual's organizational identification create a risk of generating fault lines (Lau & Murnighan, 1998 within the organization or even factions (Li & Hambrick, 2005) that may polarize subgroups within the organization and negatively influence performance outcomes.…”
Section: Organizational Identification In a Multiple-identity Contextmentioning
confidence: 99%